Juvenile Polyposis Syndrome in a Young Girl from Northern Tanzania - Jay Lodhia; David Msuya; Abdallah Msemo; Huda Akrabi; Patrick Amsi; Deborah Mchaile; Kondo Chilonga (Case Reports in Surgery)
Introduction. Juvenile polyposis syndrome is a rare autosomal dominant disorder in children characterized by multiple polyps in the gastrointestinal tract. A variety of clinical features manifest, including prolapse of a polyp or entire rectum, gastrointestinal bleeding, anaemia, and intussusception. This condition if left unmanaged promptly leads to fatal complications including the development of cancer of the bowel. Case Presentation. A 13-year-old girl with a history of mass protrusion per anus associated with bloody diarrhea. Colonoscopy showed multiple polyps in her large bowel. She underwent total colectomy with ileorectal anastomosis and did clinically well post surgery with no complications. Conclusion. Juvenile polyposis syndrome is an inherited condition with significant morbidity and a high risk of colon malignancy. It is important for early screening and diagnosis and hence management in its early stages as there are no specific standard guidelines for children.